Sustainable Biochar Production from Algal Biomass for Soil Enhancement (International Journal of Scientific Research in Science and Technology, 2024)
Biochar from algal biomass might be the way forward in improving the quality of the soil, carbon sequestration, and sustainable agriculture. The paper covers algal biochar production, characterization, and application, putting great emphasis on the fact that algal biochar may help to improve the quality of soil as it meets the economic and environmental needs. In this paper, all the diverse production methods are analyzed, along with characteristics of feedstocks, the mechanism of interaction between the soil and biochar, and so on. The remaining issues, legislation, and the near horizon scientific achievement are presented to outline more future study and profitability.